Audit quality effects of the PCAOB's 2006 tax service restrictions. (December 2021) - Notbohm, Matthew; Valencia, Adrian
Abstract: In 2004 and 2005, use of aggressive tax services provided by a company's auditor had become so broadly concerning that it was the focus of a PCAOB roundtable and discussed in a Congressional subcommittee investigation report (PCAOB, 2004 and US Senate, 2005). Although auditor provision of these and other nonaudit services to issuer audit clients was restricted in 2006, research on the effectiveness of these restrictions finds that they did not impact audit quality (Notbohm, Paterson and Valencia, 2015 and Lennox, 2016). We reexamine this issue with a focus on the audit quality effects for the engagements most impacted by the restrictions-Big 4 audit clients with pre-restriction tax service fees of at least 100, 000 that fell by at least 75% following the restrictions. Using a difference-in-difference framework and two proxies for audit quality, we find evidence of the effectiveness of the PCAOB's 2006 restrictions among those clients. Additionally, we find these results are sensitive to the level of pre-restriction tax service fees, with the restatement (going concern) effect of the restrictions strengthening (weakening) in the pre-restriction tax service fee level. We also find that the effects of these restrictions are concentrated among clients of Big 4 auditors rather than clients of the 2nd tier or 3rd tier auditors. Results of additional analyses indicate that audit quality, as measured by the probability of restatement, was lower in the pre-restriction period for purchasers than for non-purchasers. Our results are robust to a barrage of sensitivity tests. Our findings contribute to the continued regulator discussion about the proper level and types of allowable tax nonaudit services.